2022
DOI: 10.1002/ps.6845
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupler SYP‐14288 inducing multidrug resistance of Phytophthora capsici through overexpression of cytochrome P450 monooxygenases and P‐glycoprotein

Abstract: BACKGROUND: Fungicide resistance has become a serious problem for different mode of action groups except for uncouplers, which makes their resistance mechanism a hot topic, which until now, has not been well clarified. SYP-14288, a newly developed diarylamine fungicide modeled on fluazinam, has shown good toxicity to both oomycete and fungus by the action of uncoupling. In this research, the resistance of Phytophthora capsici to SYP-14288 was studied to clarify the resistance mechanism of uncouplers.RESULTS: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In particular, it was found that commercial anti-αβ-spectrin antibodies cross-reacted with elongation factor 2 and Hsp70 from Neurospora crassa and P. infestans, respectively , High-level resistance of phytopathogens to fungicides is generally caused by point mutations affecting the target protein; protein overexpression and detoxification generally result in low levels of fungicide resistance . We therefore conducted a comprehensive phylogenetic search for spectrin-like proteins in oomycetes, resulting in the identification of Pc506502 in P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was found that commercial anti-αβ-spectrin antibodies cross-reacted with elongation factor 2 and Hsp70 from Neurospora crassa and P. infestans, respectively , High-level resistance of phytopathogens to fungicides is generally caused by point mutations affecting the target protein; protein overexpression and detoxification generally result in low levels of fungicide resistance . We therefore conducted a comprehensive phylogenetic search for spectrin-like proteins in oomycetes, resulting in the identification of Pc506502 in P.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was found that commercial anti-αβspectrin antibodies cross-reacted with elongation factor 2 and Hsp70 from Neurospora crassa and P. infestans, respectively 35,26 High-level resistance of phytopathogens to fungicides is generally caused by point mutations affecting the target protein; 36−39 protein overexpression and detoxification generally result in low levels of fungicide resistance. 40 We therefore conducted a comprehensive phylogenetic search for spectrin-like proteins in oomycetes, resulting in the identification of Pc506502 in P. capsici, encoding Pcα-actinin. Despite manipulating the expression of Pcα-actinin, including knocking out the gene, the sensitivity of P. capsici to fluopicolide remained unchanged, and no point mutations were detected in the Pcα-actinin gene of resistant strains, thus excluding Pcα-actinin as the primary target of fluopicolide.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, verapamil reverted the resistance of Candida albicans to fluconazole (FLC), showed synergism with FLC against Candida albicans , and reduced fungal recovery 87 . For Phytophthora capsici on pepper, verapamil had no inhibitory effect in resistant isolates 88 . However, the MDR isolates of Phytophthora capsici could be inhibited by the EPI amitriptyline, 88 which is one substrate of P‐gp belonging to the ABC transporter superfamily 89 .…”
Section: Non‐target Site Mechanisms Of Fungicide Resistancementioning
confidence: 99%
“…For Phytophthora capsici on pepper, verapamil had no inhibitory effect in resistant isolates 88 . However, the MDR isolates of Phytophthora capsici could be inhibited by the EPI amitriptyline, 88 which is one substrate of P‐gp belonging to the ABC transporter superfamily 89 . In addition, amitriptyline can recover the activity of fluazinam, chlorothalonil, and oxathiapiprolin in Phytophthora capsici isolates 88 .…”
Section: Non‐target Site Mechanisms Of Fungicide Resistancementioning
confidence: 99%
See 1 more Smart Citation